Variation in the level of activity across the stages of the entrepreneurial startup process - evidence from 35 countries - Arenius, Pia (Estudios de Economía, 2016)
Alrich and Martínez (2001) pointed out that in “entrepreneurship many are called, but few are chosen”. Many entrepreneurs try seriously to create a lasting organization, but most of them do not pass through the three stages of the entrepreneurial startup process. There is scarce research exploring the entrepreneurial startup process, particularly studying across countries the prevalence of individuals in the different stages. This paper uses data collected across 35 countries participating in the 2005 Global Entrepreneurship Monitor (GEM) study and we examine whether individual-level factors and national culture are related to the ratio of nascent entrepreneurs to potential entrepreneurs, and to the ratio of baby business owners to potential entrepreneurs. Our results show that there is significant variation across countries in how many individuals are active in the different stages of the entrepreneurial startup process. Our results also indicate that gender and age are related to a high ratio of nascent entrepreneurs to potential entrepreneurs.